Perlindungan Hukum Terhadap Kreditor Separatis Atas Hak Eksekusi Jaminan Debitor Lembaga Keuangan Berdasarkan Undang-Undang Nomor 4 Tahun 2023 Tentang Pengembangan Penguatan Sektor Keuangan (Studi : Balai Harta Peninggalan (Bhp) Medan) - Ma’arif, Amar; Falahiyati, Nurhimmi; Sahbudi, Sahbudi (Jurnal Ilmiah Penegakan Hukum, 2025)
The position of secured creditors in the Indonesian bankruptcy regime has shifted significantly following the enactment of Law No. 4 of 2023 concerning the Development and Strengthening of the Financial Sector (UUPPSK). Separatists traditionally have the privilege of executing collateral objects without being subject to the general bankruptcy mechanisms stipulated in Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (UUKPKPU). However, the revocation of some of the UUKPKPU norms by the UUPPSK has created normative uncertainty, particularly regarding the limited access of secured creditors to bankruptcy instruments if the debtor is a financial services institution under the exclusive authority of the Financial Services Authority (OJK). Using a normative and empirical juridical approach, along with statutory, conceptual, and case study analysis, the study shows that although the UUKPKPU still legitimizes secured creditors' right to execute, its regulation is reduced by the validity of the stay period and the limitation of locus standi in financial institution bankruptcy cases. This situation creates tension between the interests of secured creditors seeking legal protection for their property rights and the regulator's goal of maintaining financial system stability. The research findings confirm that the legal configuration following the UUPPSK has not fully guaranteed the certainty and protection of secured creditors' rights, and has created a normative vacuum that has the potential to disrupt the balance between individual creditors' interests and the public interest in the context of financial sector stability.